Transcranial direct current stimulation over the posterior parietal cortex improves visuomotor performance and proprioception in the lower extremities - Kamii, Yasushi; Kojima, Sho; Onishi, Hideaki (Frontiers in Human Neuroscience, 2022)
The purpose of this study was to examine whether anodal transcranial direct current stimulation (a-tDCS) over the posterior parietal cortex (PPC) could affect visuomotor performance and proprioception in the lower extremities. We evaluated visuomotor performance in 15 healthy volunteers using a visuomotor control task by plantar dorsiflexion of the ankle joint, and calculated the absolute difference between the target and measured angle. In addition, we evaluated proprioception using a joint position matching task. During the task, the subject reproduced the ankle joint plantar dorsiflexion angle presented by the examiner. We calculated the absolute difference between the presented and measured angles (absolute error) and the variation of measured angles (variable error). Simultaneously, a-tDCS (1.5 mA, 15 min) or sham stimulation was applied to the right PPC. We observed that the absolute error of the visuomotor control task and the variable error of the joint position matching task significantly decreased after a-tDCS. However, the absolute error of the joint position matching task was not affected. This study suggests that a-tDCS over the PPC improves visuomotor performance and reduces the variable error in the joint position matching task.